2012
DOI: 10.1515/astro-2017-0361
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Studies of the Evolution of Recurrent, Symbiotic and Dwarf Novae: the White Dwarf Components are Growing in Mass

Abstract: Symbiotic binaries are systems with white dwarfs (WDs) and red giant companions. Symbiotic novae are those systems in which thermonuclear eruptions occur on the WD components. These are to be distinguished from events driven by accretion disk instabilities analogous to Dwarf Novae eruptions in Cataclysmic Variable outbursts. Another class of Symbiotic systems are those in which the WD is extremely luminous and it seems likely that quiescent nuclear burning is ongoing on the accreting WD. A fundamental question… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 26 publications
6
55
0
Order By: Relevance
“…The quiescence observations of T Pyx are inconsistent with either of these pictures Selvelli et al (2008). More recent studies have found that nova outbursts can happen on white dwarfs accreting at much higher rates than previous studies (Starrfield et al 2012;Idan et al 2013). T Pyx may be an example of such a system, although the high ejected mass is not found for most outbursts in these models.…”
Section: Discussionmentioning
confidence: 70%
“…The quiescence observations of T Pyx are inconsistent with either of these pictures Selvelli et al (2008). More recent studies have found that nova outbursts can happen on white dwarfs accreting at much higher rates than previous studies (Starrfield et al 2012;Idan et al 2013). T Pyx may be an example of such a system, although the high ejected mass is not found for most outbursts in these models.…”
Section: Discussionmentioning
confidence: 70%
“…Our detailed evolutionary calculations, as well as those of Starrfield et al (2012) and Idan et al (2013) demonstrate that a state of steady hydrogen burning does not occur. Cal 83 was observed with alternating optical/X-ray states as well, repeating every ∼ 450 days, spending about ∼ 250 days in the high state and ∼ 200 days in the low state (Rajoelimanana et al, 2013, fig.1).…”
Section: Three Candidate Pre-snmentioning
confidence: 72%
“…Each outburst ejects mass into the interstellar medium (ISM), from a few 10 −7 M to a few 10 −4 M , depending on the mass accretion rate and time necessary for the pressure at the bottom of the accreted layer to exceed the gravitational pressure. This pressure is mostly an inverse function of the WD mass (Starrfield et al 2012;Wolf et al 2013).…”
Section: Introductionmentioning
confidence: 99%